Multi-scale multi-dimensional characterization of clay-hosted pore networks of shale using FIBSEM, TEM, and X-ray micro-tomography: Implications for methane storage and migration - Zhu, Hongjian; Huang, Cheng; Ju, Yiwen; Bu, Hongling; Li, Xiaoshi; Yang, Manping; Chu, Qingzhong; Feng, Hongye; Qiao, Peng; Qi, Yu; Ma, Pinghua; Zheng, Liming; et al. (Applied clay science, 2021)
Gas shales contain a variety of clay-rich materials with multifarious pore networks. Clay-hosted porosity is an essential component and considered to play a crucial role in establishing the original hydrocarbon molecules in place and transport characteristics of the shale gas reservoir. To better understand the petrophysical basis of gas storage and migration mechanisms, we aim to visualize and quantify the nature of the clay-hosted pore networks and across micrometer and nanometer length scales. Core and outcrop samples are provided of various clay-rich shales (Qiongzhusi, Longmaxi, Wufeng, and Shihezi Formation), which are characterized using a synergistic multi-scale multi-dimensional workflow by FIBSEM, TEM, and X-ray micro-tomography (mCT). Clay-hosted pores are observed in three significant modes of occurrence depending on imaging of pores at the 2D-FIBSEM/TEM level. The first pore type is found between clay domains in clay matrix as interparticle pore, with pore size smaller than 1 μm, and includes six subtypes: type a, type b, type c, type d, type e, and type f. The second associated with the admixture belongs to inter-aggregate pore that can be further sub-divided into three classes: type g (organic-clay), type h (pyrite-clay), and type I (organic-pyrite-clay), with pore size above 50 up to 500 nm. The third associated with the clay nanoplatelets is intraparticle pore. The upper pore-size range of such pores is generally less than 1 nm, with most pores being less than 0.4 nm. Using 3D-mCT and 3D-FIBSEM, the data sets were reconstructed, clay structures were segmented and visualized, revealing the well-connected clay-hosted pore networks within the heterogeneous clay matrix and quantitatively computing pore size, pore volume, and porosity at micrometer and nanometer scales. These visual results highlight the significance of clay-hosted pore networks in shale gas reservoirs because they are the dominant controls on the petrophysical properties. The application of this workflow to worldwide clay-rich shale deposits will allow essential insights into estimating porosity and permeability of shale formations and provide insight to the storage and transport of hydrocarbon molecules from shale matrix to predict total gas resources. •We provide a synergistic workflow for clay microstructural characterization.•Gas shales contain a variety of clay-rich materials with multifarious pore networks.•Three major clay-hosted pore types are identified and classified.•Clay pores and their related capacities of storage and transport for gas are studied.